2013
DOI: 10.4000/asp.3290
|View full text |Cite
|
Sign up to set email alerts
|

CLIL in higher education: the (perfect?) crossroads of ESP and didactic reflection

Abstract: Avec l’internationalisation croissante de l’enseignement supérieur, l’Enseignement d’une matière intégré à une langue étrangère (EMILE) est devenu un objet à la fois d’enseignement et de recherche. Différents contextes internationaux fournissent des exemples de pratiques efficaces et des modèles théoriques qui incorporent des critères de qualité complexes et pertinents, tels qu’une politique linguistique institutionnelle ou nationale, une pédagogie et une didactique de l’EMILE et des rôles spécifiques des diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 13 publications
0
23
0
2
Order By: Relevance
“…Recent years have seen intensive discussion among ESP researchers in French higher education, particularly within GERAS, on the importance of reinforcing the didactic dimension of research within the French school of ESP (Taillefer 2013;Whyte 2013). As noted in section 3, and unlike general English studies, didactics was from the early days one of four key dimensions of ESP -along with linguistics, culture and technology.…”
Section: The Didasp Sig: Teaching Contexts and Research Interestsmentioning
confidence: 99%
“…Recent years have seen intensive discussion among ESP researchers in French higher education, particularly within GERAS, on the importance of reinforcing the didactic dimension of research within the French school of ESP (Taillefer 2013;Whyte 2013). As noted in section 3, and unlike general English studies, didactics was from the early days one of four key dimensions of ESP -along with linguistics, culture and technology.…”
Section: The Didasp Sig: Teaching Contexts and Research Interestsmentioning
confidence: 99%
“…Some aspects of the content integration were investigated by Taillefer (2013) who states that language and non-language content do not dominate of one over the other; it is in a balance, so that students could share their efforts and interests equally. Speaking about the aspects of communication, it is obvious that the language needed depends on the content.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the still limited attention to students' language development in CLIL, it is ESP practitioners who can address, support, and assess it properly and both ESP and CLIL are still compatible (González Ardeo, 2013;Taillefer, 2013). Yang (2016) found that ESP learners have more chances to use English in class than their CLIL peers, whereas CLIL teachers are more positive about their students' language developments than their ESP colleagues, even if they did not assess them formally.…”
Section: Esp Specialists In Clil Programmesmentioning
confidence: 99%
“…5(2)(2017): 1998). By contrast, the introduction of an additional language into the teaching of content subjects challenges the conventional roles assigned to content and language specialists and the traditional ways of designing and delivering their courses (Airey, 2016;Dafouz, Hüttner, & Smit, 2016;Skinnari & Bovellan, 2016;Taillefer, 2013). Although disciplinary language, skills, and genres in English are increasingly present in content subjects, subject experts tend to concentrate on disciplinary concepts, skills, and mind-sets and treat language merely as a tool for content learning and discipline-related tasks and not as an aim that requires explicit attention, language pedagogy, or assessment (Airey, 2016;Jacobs, 2005Jacobs, , 2007Yang, 2016;Zhang, 2016).…”
Section: Esp Specialists In Clil Programmesmentioning
confidence: 99%
See 1 more Smart Citation